1996
DOI: 10.1107/s0907444995009280
|View full text |Cite
|
Sign up to set email alerts
|

Structure determination and refinement of the Humicola insolens endoglucanase V at 1.5 Å Resolution

Abstract: The structure of the catalytic core of the endoglucanase V (EGV) from Humicola insolens has been determined by the method of multiple isomorphous replacement at 1.5 A, resolution. The final model, refined with X-PLOR and PROLSQ, has a crystallographic R factor of 0.163 (Rfree = 0.240) with deviations from stereochemical target values of 0.012 ,~ and 0.037 ° for bonds and angles, respectively. The model was further refined with SHELXL, including anisotropic modelling of the protein-atom temperature factors, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 37 publications
(45 reference statements)
2
38
0
2
Order By: Relevance
“…A BLAST search of the amino acid sequence of PcCel45A showed that the protein may be classified into the GH family 45, which includes many small EGs (8,9,11,36), and this conclusion is supported by the result of hydrophobic cluster analysis (performed by B. Henrissat, personal communication). Since only a low sequence similarity was found with other known GH family 45 EGs, the protein represents a new subdivision of this family.…”
Section: Discussionsupporting
confidence: 51%
“…A BLAST search of the amino acid sequence of PcCel45A showed that the protein may be classified into the GH family 45, which includes many small EGs (8,9,11,36), and this conclusion is supported by the result of hydrophobic cluster analysis (performed by B. Henrissat, personal communication). Since only a low sequence similarity was found with other known GH family 45 EGs, the protein represents a new subdivision of this family.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, they were rinsed in Milli-Q water and heattreated at 150 • C for 60 min. The films prepared in this way [33], here shown in complex with cellohexaose, and a carbohydrate-binding module (B) [34], here represented by the carbohydrate-binding module (CBM) of Cel7A (Trichoderma reesei), belonging to the same classification family. The CBM is connected to the C-terminal of the catalytic core.…”
Section: Cellulose Substratesmentioning
confidence: 99%
“…The native enzyme consists of two parts, a catalytic core containing 213 amino acids ( Fig. 1A [33]) and a C-terminal carbohydrate-binding module (CBM) containing 38 amino acids ( Fig. 1B [34]), held together by a linkage containing 33 amino acids [29].…”
Section: Chemicalsmentioning
confidence: 99%
“…(images are taken from the RCSB PDB (www.pdb.org). The following labels correspond to PDB accession numbers: ‘Hexokinase’ - 1ig8[43]; ‘GH5, GH44, GH51’ - 1e5j[44]; ‘GH6’ - 2boe[45]; ‘GH7, GH12’ - 2jen[46]; ‘GH8, GH9, GH48’ - 1ia6[47]; ‘GH23’ – 2xqo[33]; ‘GH45’ - 4eng[48]; ‘GH61’ - 2vtc[49]; ‘GH74’ - 2cn2[50]. …”
Section: Figurementioning
confidence: 99%